Towards a framework for the intersection of environmental justice and climate change - Eisenhauer, Emily, author; Julius, Susan, author (Colorado State University. Libraries, 2017)
In 1994, the Interagency Working Group on Environmental Justice (EJIWG) was established by Executive Order 12898 to advance environmental justice principles. In 2011 the EJIWG identified climate change as an important area of focus for increased reporting and for joint development of programs with impacted communities. To achieve these goals, a working group came together to develop a framework that articulates the intersection of EJ and climate change, provides a basis for using common terminology to support federal actions, supports the engagement of communities often left out of climate change conversations, and identifies needs and gaps to inform targeted education, communication, and implementation actions. A list of key terms was compiled from across the climate change science and climate justice research and community based work, as well as from community planning. Key questions that guided the development of the framework were: who is most vulnerable to climate change, and how? How does climate change interact with existing environmental justice disparities? How can disparities arising from the added effects of climate change be reduced, and how can opportunities arising from actions to mitigation and adapt to climate change be leveraged to reduce vulnerability? The framework draws on long- and well-established federal environmental justice programs that seek to reduce disparities in environmental impacts, and integrates more recent actions to address the impacts of climate change. It serves the goals of the EJIWG by illustrating how climate change and environmental justice issues interact to contribute to vulnerability, and how adverse outcomes can be minimized and beneficial outcomes maximized. Meaningful involvement of affected communities is a key factor in leading to these desired outcomes through maximizing co-benefits and utilizing equitable development.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: EPA; EJIWG; Federal Interagency Working Group on Environmental Justice; climate change; environmental justice; adaptation; mitigation